(untitled) (Oxford, 1974)
Extensively revised and updated, this manual describes and discusses techniques that are suitable for the chemical analysis of soils, plant materials, animal tissue and fresh waters. Some of the simpler procedures are given, but most modern instrumental techniques are also dealt with in detail. Procedures are described for certain pollutants of current interest, including heavy metals, and pesticides. Other background information includes discussions on sample collection, initial treatments and statistical considerations, whilst the appendices include a variety of data on the chemical composition of natural biomaterials.
Keywords: Chemistry, Analytic,Soils,Plants,Water; Analysis,Analysis,Analysis